How to get rate of change

In this blog post, we will provide you with a step-by-step guide on How to get rate of change.

Rate of Change

In a mathematical sense, the Average Rate of Change of a function over a interval is given as the ratio of change in the function over the interval to the change in the value of the endpoints. The

Explain math questions

Fast answers

In a world where we can get answers to our questions faster than ever before, it's important to have a source that can give us the information we need quickly and accurately.

Do my homework

Download full explanation

The best way to learn about different cultures is to travel and immerse yourself in them.

Determine math equation

Improve your theoretical performance

If you want to improve your performance, you need to focus on your theoretical skills.

Do mathematic equation

Introduction to average rate of change (video)

How to Find Average Rates of Change Quick Overview For the function, f ( x), the average rate of change is denoted Δ f Δ x. In mathematics, the Greek letter Δ (pronounced del-ta) means
Get Started

Rate of Change Formula & Examples

The rate of change formula gives the relationship describing how one quantity changes in relation to the change in another quantity. The rate of change from the coordinates of y to coordinates of x can found out as Δy/ Δx = (y 2 - y 1 )/ (x 2 - x 1 ). For a linear function, the rate of change m is represented in the slope-intercept form for a line: y=mx+b whereas the rate of change of functions is otherwise defined as, (f (b)-f (a))/ b-a.

Determine math question

Get help from expert professors

If you need help with your homework, our expert writers are here to assist you.

Explain mathematic


Call now and get service instantly!


Do math equations

Doing math equations is a great way to keep your mind sharp and improve your problem-solving skills.

Solve math

Enhance your theoretical performance

To enhance your theoretical performance, consider using a study guide.

Rates of Change

f (x) = x 2 – 9x. a = 2. b = 7. f (a) = f (2) = (2) 2 – 9 (2) = 4 – 18 = -14. f (b) = f (7) = (7) 2 – 9 (7) = 49 – 63 = -14. The average rate of change is: A ( x) = f ( b) − f ( a) b − a = − 14 − ( − 14) 7 − 2 = −